Effect of irrigation and foliar spray of nutrients on growth and seed yield of gram (Cicer arietinum) - SRIVASTAVA, G P; SRIVASTAVA, V C (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during the winter seasons of 1987-90 to study the effect of irrigation and foliar spray of nutrients on growth and yield of ’H 208’ gram (Cicer arietinum L.). Irrigation at branching and pod-filling stages along with foliar application of 2% urea at 50% flowering gave the highest seed yield (1.7 tonnes/ha), the N, P and K uptake and water-use efficiency compared with othertreatment combinations of foliar application (2% triple superphosphate, 2% potassium sulphate. water spray and no spray) and irrigation (no irrigation, 1 irrigation at branching. 1 irrigation at pod-filling stage and 2 irrigations at the branching and pod-filling stages).